LAPAROSCOPIC CHOLECYSTECTOMY: AN AUDIT OF 500 PATIENTS - Mehraj, Adnan; Naqvi, Muhammad Ali; Feroz, Shizan Hamid; Rasheed, Haroon ur (Journal of Ayub Medical College Abbottabad, 2011)
Background: The Gold standard treatment for symptomatic gallstone disease is laparoscopic cholecystectomy (LC) since 1990. LC can be performed safely as a day case procedure. The objective of this study was to evaluate the results of laparoscopic cholecystectomy in symptomatic gall stones disease in terms of length of hospital stay, complications, morbidity and mortality. Methods: This retrospective descriptive study was carried out in Department of General & Laparoscopic Surgery, AK CMH, Muzaffarabad. Notes of all patients who underwent laparoscopic cholecystectomy in the department over a 26 month period were reviewed from department register. Demographics as well as details of cases, conversion to open operation and complications of surgery and anaesthesia were reviewed from clinical notes and departmental register and noted on a designed Performa. Data were analysed using SPSS-18 and results compared with international studies. Results: Out of 500 patients, 443 (88.6%) were females and 57 (11.4%) were males. The mean age of the patients was 42.47±11.43 years. Mean operative time was 40.09±11.16 minutes. Seven (1.4%) patients developed port site wound infection. Sixteen (3.2%) cases were converted to open surgery in face of obscured anatomy of Calot’s triangle. Two (0.4%) cases has cystic duct stoma leak secondary to missed Common duct stones and were dealt with ERCP and stone extraction. There was no case of bile duct injury, major haemorrhage or bowel injury. There was no mortality associated with laparoscopic cholecystectomy in our series. Conclusion: Laparoscopic cholecystectomy is a safe and effective management of gall stone disease. Better training, careful case selection, meticulous technique and high standard equipment are of paramount importance for ensuring good results in laparoscopic cholecystectomy. Keywords: Laparoscopic cholecystectomy, complications, cystic duct leak, bile duct injury, gall stone